68 Implementation of the 'School Travel Safety Survey' for Data Linkage Research. (1st September 2016) - Fry, Richard; Turner, Samantha; Rodgers, Sarah; Lyons, Ronan; Mackay, Morag; Vincenten, Joanne; Griffiths, Helen
Abstract : Background: The School Travel and Child Safety Survey (STCSS) was developed as part of the European TACTICS project (Tools to Address Childhood Trauma, Injury and Children's Safety) to address the lack of standardised data on children's safety and exposure to risk across Europe. Description of the Problem: Current methods used to collect data on child safety and exposures to risk are not collected in a coordinated way, making research and policy evaluation in these areas difficult. The STCSS was developed with European partners, as a standardised tool which could be adopted by member states, to collect child safety data and enable comparisons between different regions/countries for policy development and evaluation. Travel behaviour data (e.g. mode of transport and distance travelled) is also limited; but vitally important for monitoring active travel and road safety interventions. Results: The STCSS was developed for children aged 10–13 years to be undertaken in school, and was successfully piloted in 5 countries across Europe (n = 636, participation rate = 88.37%). A sample of children were retested to establish the survey reliability, and per cent agreements were ≥96%. The STCSS has been further developed in Wales, to enable the results to be anonymised and incorporated into the Secure Anonymised Information Linkage (SAIL) databank at Swansea University. Data linkage methods within SAIL allow the STCSS results to be linked to other individual and household level datasets; for example, socioeconomic, demographic, health and education data. Conclusions: The ability to link the results from this survey to other routinely collected data in the SAIL database, will provide much needed evidence on the medium and long-term effectiveness of child safety interventions and policies; as well as provide regional, national and international policy makers with data to support the planning and evaluation of interventions.